Ultrasonic vibrations in liquid medium in flexible polyamide tube of small diameter - A. A. Novikov; D. A. Negrov; A. R. Putintseva; V. Yu. Putintsev; A. A. Krutko; D. D. Sidorenko (Омский научный вестник)
The purpose of this article is to study the characteristics of the passage of ultrasonic oscillations in a liquid medium through an extended plastic tube of small diameter. The article presents the design of the research stand and the results of studies of the characteristics of the passage of ultrasonic vibrations in a liquid medium through polyamide urological stents of small diameters. The tasks solved here are the determination of the influence of such factors as the density of the medium and the size of the cross section of the tube on the level of intensity of ultrasonic vibrations in the tube. It is shown that in this case the speed of propagation of an ultrasonic wave in a liquid medium decreases sharply. In addition, along the length of the tube, the wave nonuniformity of the intensity of ultrasonic vibrations is formed, which must be taken into account when using the ultrasonic cleaning of the internal surfaces of such tubes.